Liturgical Scrolls of Southern Italy as a Special Type of Illuminated Manuscripts - Kovalevskaia, Svetlana V. (Actual Problems of Theory and History of Art, 2015)
The article is devoted to illustration principles of Southern Italian liturgical scrolls, a specific type of manuscripts manufactured only in this region within the period from 10th to 14th century. Only thirty one scrolls have been preserved. The overview is made based on iconographic and stylistic analysis of the material, which includes the following key points: connection between the illustrative programme and the peculiarities of the Southern Italian liturgical practice, a correspondence between texts and illustrations, the illustrative programme changes caused by the prohibition of the old and the emergence of the new edition of the Easter hymn text. The author classifies illustrations by their plots, and points out principal features of this stylistically diverse material. Briefly described are stylistic and iconographic distinctions that enable us to arrange certain manuscripts in groups, each of which tends to stick to one or another art centre. The author states that due to the region’s unique historical and geographical position, each scroll stands out as the unique synthesis of different artistic traditions, which primarily are Carolingian, Ottonian and Byzantine.